2008
DOI: 10.1001/archneur.65.12.1604
|View full text |Cite
|
Sign up to set email alerts
|

Functional Abnormalities Underlying Pathological Gambling in Parkinson Disease

Abstract: Background: Pathological gambling (PG) may develop in patients with Parkinson disease (PD) during dopamine replacement therapy, but the underlying neural correlates are still unclear.Objective: To investigate resting state brain perfusion in PD patients with active PG compared with matched PD controls and healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
88
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 32 publications
10
88
2
4
Order By: Relevance
“…Thus, in our case, it may be possible that the parahippocampal gyrus may contribute to the emotional salience associated with the decision making process. This is also consistent with previous studies demonstrating the involvement of this region in impulsive behaviour (Völlm et al 2007;Soloff et al 2008;Carmona et al 2005;Cilia et al 2008). …”
Section: Discussionsupporting
confidence: 93%
“…Thus, in our case, it may be possible that the parahippocampal gyrus may contribute to the emotional salience associated with the decision making process. This is also consistent with previous studies demonstrating the involvement of this region in impulsive behaviour (Völlm et al 2007;Soloff et al 2008;Carmona et al 2005;Cilia et al 2008). …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, age correlates with the line bisection errors found in the current study were consistent with many previous reports [17], implying an age-related and right-(facial decision task) hemispheric dominant tasks [41]. Right hemisphere dominance is also found in over-eating behavior [42][43][44], which is considered a behavioral addiction [45,46]. This pattern of hemispheric dominance is also depicted in patients with Parkinson's disease and pathological gambling, by perfusion single-photon emission computed tomography [47].…”
Section: Discussionsupporting
confidence: 92%
“…Right hemisphere dominance is also found in over-eating behavior [42][43][44], which is considered a behavioral addiction [45,46]. This pattern of hemispheric dominance is also depicted in patients with Parkinson's disease and pathological gambling, by perfusion single-photon emission computed tomography [47]. Further, the obsessive-compulsive trait represents a major risk of headache chronification and drug dependence [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, one cannot rule out that the individual vulnerability to develop behavioral addictions also stems from neurobehavioral mechanisms that are not related to mesolimbic dopamine. In the absence of an external task (ie freely fluctuating brain activity), PD patients experiencing heavy PG symptoms at the time of study showed increased brain perfusion in dopaminergic mesolimbic structures, but also in the insula, the hippocampus, and the amygdala (Cilia et al, 2008). More studies are needed in this area to distinguish traits that predict vulnerability from an abnormal neurobehavioral pattern that may evolve once PG consolidates as a behavior.…”
Section: Discussionmentioning
confidence: 99%